Circadian Rhythms in Floral Scent Emission - Fenske, Myles P.; Imaizumi, Takato (Frontiers in Plant Science, 2016)
To successfully recruit pollinators, plants often release attractive floral scents at specific times of day to coincide with pollinator foraging. This timing of scent emission is thought to be evolutionarily beneficial to maximize resource efficiency while attracting only useful pollinators. Temporal regulation of scent emission is tied to the activity of the specific metabolic pathways responsible for scent production. Although floral volatile profiling in various plants indicated a contribution by the circadian clock, the mechanisms by which the circadian clock regulates timing of floral scent emission remained elusive. Recent studies using two species in the Solanaceae family provided initial insight into molecular clock regulation of scent emission timing. In Petunia hybrida, the benzenoid/phenylpropanoid (FVBP) pathway is the major metabolic pathway that produces floral volatiles. Three MYB-type transcription factors, ODORANT1 (ODO1), EMISSION OF BENZENOIDS I (EOBI), and EOBII, all of which show diurnal rhythms in mRNA expression, act as positive regulators for several enzyme genes in the FVBP pathway. Recently, in P. hybrida and Nicotiana attenuata, homologs of the Arabidopsis clock gene LATE ELONGATED HYPOCOTYL (LHY) have been shown to have a similar role in the circadian clock in these plants, and to also determine the timing of scent emission. In addition, in P. hybrida, PhLHY directly represses ODO1 and several enzyme genes in the FVBP pathway during the morning as an important negative regulator of scent emission. These findings facilitate our understanding of the relationship between a molecular timekeeper and the timing of scent emission, which may influence reproductive success.